Additively manufactured Ti6Al4V with controlled surface structure as a potential material for joint implants: Long-term wear performance and durability - Odehnal, Lukáš; Ranuša, Matúš; Čípek, Pavel; Malý, Martin; Mazánová, Veronika; Dlouhý, Antonín; Koutný, Daniel; Hartl, Martin; Vrbka, Martin (Elsevier, 2025)
In this study, a comprehensive investigation of long-term wear and extended fluorescent experiments was supported by microstructural and chemical analysis. The aim was to compare the differences between a 3D printed Ti6Al4V alloy with a controlled surface structure created directly during the 3D printing process with a conventionally manufactured CoCr30Mo6 alloy. The primary equipment consisted of two tribometers with a pin-on-plate configuration. This enabled conducting these two types of experiments under kinematic and load conditions closely resembling in vivo environments. The Ti6Al4V alloy consistently outperformed the conventional alloy, showing lower wear of the UHMWPE plate and the tested pins. Additionally, fluorescence microscopy revealed that lubrication film formation was more stable for Ti6Al4V, with longer retention of all model synovial fluid constituents in the contact area. The results demonstrate the potential of 3D printed Ti6Al4V alloy as a material for frictional surfaces in joint implants. However, there are still opportunities for improvement, such as applying coatings to enhance performance.
Keywords: 3D printed Ti6Al4V; Fluorescence microscopy; Long-term wear; Surface structures